2020
DOI: 10.1001/jamainternmed.2020.4199
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fluoroquinolones With the Risk of Aortic Aneurysm or Aortic Dissection

Abstract: IMPORTANCE Previous observational studies have suggested that fluoroquinolones are associated with aortic aneurysm or dissection, but these studies may be subject to confounding by indication or surveillance bias.OBJECTIVE To assess the association of fluoroquinolones with risk of aortic aneurysm or aortic dissection (AA/AD) while accounting for potential confounding by fluoroquinolone indication and bias owing to differential surveillance. DESIGN, SETTING, AND PARTICIPANTSIn an observational cohort study usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 28 publications
3
53
0
4
Order By: Relevance
“…In a previous study, the use of fluoroquinolone was associated with a two-to three-fold higher risk of aortic dissection, with the risk increasing 10 days after fluoroquinolone exposure (1). Recent studies have reported data that support that it is not fluoroquinolone exposure, but other factors that are associated with aortic dissection in patients who receive fluoroquinolone to treat infections (3, 4), however, even those studies could not fully rule out a causal relationship between fluoroquinolones and aortic dissection in certain patients (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the use of fluoroquinolone was associated with a two-to three-fold higher risk of aortic dissection, with the risk increasing 10 days after fluoroquinolone exposure (1). Recent studies have reported data that support that it is not fluoroquinolone exposure, but other factors that are associated with aortic dissection in patients who receive fluoroquinolone to treat infections (3, 4), however, even those studies could not fully rule out a causal relationship between fluoroquinolones and aortic dissection in certain patients (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…По данным популяционного продольного когортного исследования, проведенного в Канаде [12], общий относительный риск развития аневризмы аорты при терапии ФХ у пациентов старше 65 лет составил 2,72 (95% ДИ 2,53-2,93). Существенную роль в более частом развитии нежелательных реакций у лиц старшей возрастной группы играет полиморбидность [7,17].…”
Section: клинико-морфологические формы и факторы риска поражения аорты при терапии фторхинолонамиunclassified
“…Аневризма аорты наиболее часто развивается на фоне атеросклеротического поражения [7,9,[25][26][27], риски которого максимальны у пациентов пожилого и старческого возраста, курящих, пациентов с дислипидемией, генетической предрасположенностью, нарушениями липидного обмена и сердечно-сосудистыми катастрофами в семейном анамнезе [7,21,25,28]. Риск развития аневризмы брюшной аорты значительно выше у курящих пациентов, чем у некурящих [29].…”
Section: клинико-морфологические формы и факторы риска поражения аорты при терапии фторхинолонамиunclassified
See 2 more Smart Citations